1993
DOI: 10.1121/1.406092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simulated aircraft noise on heart rate and behavior of desert ungulates

Abstract: The effects of simulated low-altitude jet aircraft noise on the behavior and physiology of 6 captive desert mule deer (Odocoileus hemionus crooki) and 5 mountain sheep (Ovis canadensis mexicana) were evaluated. Heart rate and behavior in relation to ambient temperature, number of simulated overflights/day, and noise levels [range =92–112 decibels (dB)] that the animals were exposed to were measured. Heart rates during simulated overflights (n=112/treatments/season) were compared to data collected prior to and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
1999
1999

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Numerous studies have found that aircraft noise startles and disrupts animals and potentially affects both nesting and migratory patterns. 2 The U.S. Fish and Wildlife Service contends that military overflights disrupt wildlife on over 35 national wildlife refuges.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found that aircraft noise startles and disrupts animals and potentially affects both nesting and migratory patterns. 2 The U.S. Fish and Wildlife Service contends that military overflights disrupt wildlife on over 35 national wildlife refuges.…”
Section: Introductionmentioning
confidence: 99%